The Role Of Environmental Concern In Mediating Promotion And Brand Image Of Electric Vehicle Purchase Intention In Denpasar City - Ni Kadek Linda Surlimna; Made Setini; Ni Made Wahyuni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of environmental concern in mediating the influence of promotion and brand image on the purchase intention of electric vehicles in the city of Denpasar. The method used was a survey by collecting data through a questionnaire distributed to 160 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study show that promotion has a positive and significant influence on purchase intention and environmental concern. Brand image has a positive but not significant effect on purchase intention and environmental concern. In addition, environmental concern has proven to have a positive and significant effect on purchase intention. The results also show that environmental concern plays a role as a partial mediator in the relationship between promotion and purchase intention, but does not mediate the relationship between brand image and purchase intention. This finding provides insight for automotive companies in designing more effective marketing strategies by prioritizing environmental issues and brand image to increase purchase intention of electric vehicles.